Narrator and Modality in Frau Holle's Fairy Tale - Utami, Alvidya Nisa; Pratita, Ina Ika; Nasrullah, Riki; Sodiq, Syamsul; Kurniawati, Wisma (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
The fairy tale Frau Holle by the Brothers Grimm presents a distinctive narrative structure, featuring an omniscient narrator and a strong moral message conveyed both implicitly and explicitly. This study addresses the characteristics of the narrator and the forms of modality used to construct meaning within the text. The research aims to examine the narrator's role in storytelling and to identify the types of modality it contains. A qualitative method is applied, using content analysis on relevant narrative excerpts from the fairy tale.The results indicate that the narrator is heterodiegetic and omniscient, which allows the narrative to be delivered with seeming objectivity while remaining laden with normative judgments. The dominant modalities are deontic (relating to obligation and prohibition) and epistemic (relating to certainty and possibility). These are used strategically to shape the reader's perception of characters, their actions, and the consequences they receive. Moreover, these modalities reinforce moral values such as hard work, obedience, and justice, which form the foundation of the story's ethical message. This study finds that the narrator and modality play a significant role in shaping meaning, moral evaluation, and the educational function of traditional literary texts.